Ab initio derivation of Hubbard models for cold atoms in optical lattices - Walters, R; Cotugno, G; Johnson, T; Clark, SR; Jaksch, D (2013)
We derive ab initio local Hubbard models for several optical lattice potentials of current interest, including the honeycomb and Kagomé lattices, verifying their accuracy on each occasion by comparing the interpolated band structures against the originals. To achieve this, we calculate the maximally-localized generalized Wannier basis by implementing the steepest-descent algorithm of Marzari and Vanderbilt [N. Marzari and D. Vanderbilt, Phys. Rev. B 56, 12847 (1997)] directly in one and two dimensions. To avoid local minima we develop an initialization procedure that is both robust and requires no prior knowledge of the optimal Wannier basis. The MATLAB code that implements our full procedure is freely available online at http://ccpforge.cse.rl.ac.uk/gf/project/mlgws/.